Pengaruh Komite Audit dan Financial Distress terhadap Integritas Laporan Keuangan - Sunardi Sunardi; Fenti Astrina (Balance : Jurnal Akuntansi dan Bisnis, 2025)
Research Objectives, to explore the effective audit committee can improve the integrity of financial reports, and financial distress conditions can affect the integrity of financial reports. Research methodology, data used secondary data, population and sample of 18 companies with 4 years of observation (72 observations), data analysis method panel data regression with stata. The results of the analysis show that the audit committee in carrying out its duties and functions focuses on supervising the implementation of regulations and the implementation of accounting standards so that financial reports are presented honestly, transparently and accountably. Furthermore, in conditions of financial distress, it does not think about engineering financial reports, as evidenced by the financial distress score> 1. While the size of the company as a control variable is also not seen, the size of small and large companies is different in the preparation of financial reports. The conclusion is that the audit committee has an effect on the integrity of financial reports, then financial distress and company size do not affect the integrity of financial reports.